Pengaruh Penggunaan Media Pembelajaran Berbasis YouTube dalam Meningkatkan Minat Belajar Siswa pada Mata Pelajaran Ekonomi - Linda Purnamawati; Marazaenal Adipta; Sahabudin Sahabudin (Tirai Edukasi : Jurnal Pendidikan, 2026)
This study aims to determine the influence of YouTube-based learning media on students’ learning interest in Economics at SMA Negeri 1 Pringgarata. The research applied a one-group pretest-posttest experimental design with a sample of 36 eleventh-grade students. The research instrument was a learning interest questionnaire consisting of 15 Likert-scale items that had been tested for validity and reliability (? = 0.834). Data were collected through pretest and posttest, then analyzed using the Shapiro-Wilk normality test and paired sample t-test. The findings showed an increase in the average score from 47.61 (pretest) to 67.42 (posttest), with a mean difference of 19.81. The paired sample t-test result was t(35) = 19.577, p < 0.001. Indicating a significant practical effect. Therefore, YouTube-based learning media proved effective in enhancing students’ interest in learning Economics.